Experimental IR Meets Multilinguality, Multimodality, and Interaction : 8th International Conference of the CLEF Association, CLEF 2017, Dublin, Ireland, September 11-14, 2017, Proceedings /: 8th International Conference of the CLEF Association, CLEF 2017, Dublin, Ireland, September 11-14, 2017, Proceedings. (2017) - Unknown
No abstract available